"Holostei versus Halecostomi" Problem: Insight from Cytogenetics of Ancient Nonteleost Actinopterygian Fish, Bowfin Amia calva - Majtánová, Zuzana; Symonová, Radka; Arias-Rodriguez, Lenin; Sallan, Lauren; Ráb, Petr (Journal of experimental zoology. Part B, Molecular and developmental evolution, 2017)
Bowfin belongs to an ancient lineage of nonteleost ray-finned fishes (actinopterygians) and is the only extant survivor of a once diverged group, the Halecomorphi or Amiiformes. Owing to the scarcity of extant nonteleost ray-finned lineages, also referred as "living fossils," their phylogenetic interrelationships have been the target of multiple hypotheses concerning their sister group relationships. Molecular and morphological data sets have produced controversial results; bowfin is considered as either the sister group to genome-duplicated teleosts (together forming the group of Halecostomi) or to gars (Lepisosteiformes; together forming the group of Holostei). However, any detailed cytogenetic analysis of bowfin chromosomes has never been performed to address this issue. Here we examined bowfin chromosomes by conventional (Giemsa-staining, C-banding, base-specific fluorescence and silver staining) and molecular (FISH with rDNA probes) cytogenetic protocols. We identified diploid chromosome number 2n = 46 with a middle-sized submetacentric chromosome pair as the major ribosomal DNA-bearing (45S rDNA), GC-positive and silver-positive element. The minor rDNA (5S rDNA) sites were localized in the pericentromeric region of one middle-sized acrocentric chromosome pair. Comparison with available cytogenetic data of other nonteleost actinopterygians (bichirs, sturgeons, gars) and teleost species including representative of basally branching lineages showed bowfin chromosomal characteristics more similar to the teleost type than to any other nonteleosts. Particularly striking differences were identified between bowfin and gars, the latter of which were found to mimic mammalian AT/GC genomic organisation. Such conclusion however contradicts the most recent phylogenomic results and raises the question what states are ancestral and what are derived.
Keywords: ryby; cytogenetika; Fishes; Cytogenetics; Animals; karyotyp; biologická evoluce; Biological Evolution; zvířata; Karyotype